PEMAHAMAN JAMAAH TABLIGH DI KOTA PADANG PANJANG TERHADAP QS. AT-TAUBAH AYAT 2 DAN RELASI TERHADAP KHURUJ FI SABILILLAH (STUDI LIVING QURAN) - M. Ridho Aulia (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Abstract.. As for the background of the researcher discussing the Khuruj problem that is in the Al Qur'an surah At-Taubah verse 2, it is explained that; Then walk you (the polytheists) on the face of the earth for four months. On this basis, the researchers saw Jamaah Tabligh quoting this verse as a proof for khuruj fi sabilillah. Therefore, the researcher wants to know how the understanding of jama'ah tabligh in the city of Padang Panjang regarding Q.s at-taubah verse 2 and its relation to khuruj fi sabilillah. This study uses a qualitative method based on living Quran, namely field research by describing a phenomenon that occurs in people who see how the application of the Qur'anic verse, while the informants of this study are the Amir jama'ah tabligh who carry out khuruj fi sabilillah. In collecting data, researchers used observation, interview and documentation techniques. The results of this study concluded that they looked more at the literal-textual aspect, rather than the substantive-contextual meaning. This can be seen from the 3 verses which he used as the main basis for preaching in the QS. Ali Imran [3]: 104 and 110, as well as the arguments for khuruj written in QS. Al-Taubah [9]: 2.